Seasonal dynamics of Arctic soils: Capturing year-round processes in measurements and soil biogeochemical models - Lyu, Zhou; Sommers, Pacifica; Schmidt, Steven, K; Magnani, Marta; Cimpoiasu, Mihai; Kuras, Oliver; Zhuang, Qianlai; Oh, Youmi; de la Fuente, Maria; Cramm, Margaret; Bradley, James, A (Earth-Science Reviews, 2024)
International audience